2005
DOI: 10.1007/s10750-005-5444-z
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Chironomidae (Insecta: Diptera) Head Capsules in Recent Sediments of Canadian Arctic Lakes

Abstract: Thirty-two taxa of chironomid larvae were collected from the sediments of 50 lakes from across the Canadian Arctic Islands. Most chironomid taxa living in the Arctic have wide distributions, with only one taxon, Abiskomyia, showing a clear geographic limitation in this region. Many of these taxa have habitat preferences, among which lake morphometry, pH, nutrients and temperature are important. Due to the complex environmental patterns in the Arctic, lakes in both the northern and southern portion of the Canad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
49
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(51 citation statements)
references
References 38 publications
2
49
0
Order By: Relevance
“…2b, 2d, and S2; Table S3). Gajewski et al (2005) found that C. ambigua is prevalent in lakes with forested catchments and relatively high DOC concentration. High relative abundance of Glyptotendipes and C. ambigua has also been reported for forested lakes across the central Canadian treeline (Walker and MacDonald 1995).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…2b, 2d, and S2; Table S3). Gajewski et al (2005) found that C. ambigua is prevalent in lakes with forested catchments and relatively high DOC concentration. High relative abundance of Glyptotendipes and C. ambigua has also been reported for forested lakes across the central Canadian treeline (Walker and MacDonald 1995).…”
Section: Discussionmentioning
confidence: 97%
“…For chironomids, water temperature is often described as the primary factor that governs the community structure of northern and alpine lakes (Walker et al 1991;Lotter et al 1997;Fortin et al 2015). Water chemistry is also known to have some influence (Gajewski et al 2005;Medeiros and Quinlan 2011;Luoto et al 2016). For example, nutrients enhance aquatic production and lead to change in chironomid community composition via alteration of food supply and habitat availability .…”
Section: Partitioning Variation In Biological Community Compositionmentioning
confidence: 99%
“…Zooplankton communities within the lakes are dominated by pelagic Copepoda (Cyclopoda) species [20]. Benthic invertebrates are typically limited to a few species of Diptera (Chironomidae) [22], and Arctic char occupy the top trophic position of these systems, with some individuals displaying cannibalistic behavior, as known for European High Arctic systems [23]. In southern Arctic lakes, Gammaridae and Trichoptera may be present [24].…”
Section: Introductionmentioning
confidence: 99%
“…A strong relationship between chironomid species assemblages and mean summer air temperature has been reported from many regions around the world and transfer functions were subsequently developed (e.g. Brooks and Birks, 2001;Larocque et al, 2001;Heiri et al, 2003;Gajewski et al, 2005;Barley et al, 2006;Woodward and Shulmeister, 2006;Langdon et al, 2008;Rees et al, 2008;Eggermont et al, 2010;Luoto, 2009;Holmes et al, 2011;Heiri et al, 2011;Chang et al, 2015a). The application of these transfer functions has provided quantitative temperature data since the last glacial period in many regions of the world (e.g.…”
Section: E Zhang Et Al: a Chironomid-based Mean July Temperature Inmentioning
confidence: 99%